Pengaruh Perputaran Kas, Loan to Deposit Ratio, dan Pertumbuhan Jumlah Nasabah Terhadap Profitabilitas - Puspadewi, Ni Kadek Dealita; Satriya, I Wayan Budi (Hita Akuntansi dan Keuangan, 2024)
The purpose of this study was to examine the effect of cash turnover, loan to deposit ratio, and growth in the number of customers on profitability during the Covid-19 pandemic in savings and loan cooperatives throughout the Pedungan Village. The population used in this study were 30 savings and loan cooperatives throughout the Pedungan Village. Determination of the sample using a purposive sampling technique to obtain 10 companies as a sample, with 3 years of observational data to obtain 30 observational data. Data were analyzed using multiple linear regression analysis. The results of the analysis show that cash turnover has no effect on profitability, the load to deposit ratio has a positive and significant effect on profitability, and growth in the number of customers has no effect on profitability during the Covid-19 pandemic in savings and loan cooperatives throughout the Pedungan Village.